Assessment of Developmental Prosopagnosia in an Individual with Tourette Syndrome and Attention Deficit Hyperactivity Disorder: A Case Report - Petter Espeseth Emhjellen; Randi Starrfelt; Rune Raudeberg; Bjørnar Hassel (Brain Sciences)
Background/Objectives: Prosopagnosia is the inability to recognize people by their faces. Developmental prosopagnosia is the hereditary or congenital variant of the condition. The aim of this study was to demonstrate the assessment of developmental prosopagnosia in a clinical context, using a combination of commercially available clinical assessment tools and experimental tools described in the research literature. Methods: We conducted a comprehensive neuropsychological assessment of a man with Tourette syndrome and attention deficit hyperactivity disorder (ADHD). The patient (ON) had experienced difficulties with face identity recognition throughout his life but believed they were caused by a lack of interest in others. Results: The neuropsychological assessment revealed varying degrees of difficulties primarily related to executive functions, attention, reaction time, and memory processes, as expected in a person with Tourette’s syndrome and ADHD. In addition, ON reported severe problems with face recognition on a prosopagnosia questionnaire and demonstrated severely impaired performance on tests of face memory and face perception commonly used to diagnose prosopagnosia. Interestingly, he reported familial face recognition problems on the maternal side of the family, while tics and ADHD symptoms occurred on the paternal side. This suggests that, in this case, the conditions were likely inherited through different genetic pathways. Conclusions: Proper assessment of face recognition problems, which includes a broad spectrum of clinical assessment tools, could help patients develop awareness and acceptance of themselves and their difficulties, and could serve as a basis for the development of clinical interventions. While ON’s DP, Tourette syndrome, and ADHD may have distinct genetic origins, impairment in face identity recognition has been observed across several neurodevelopmental conditions and is likely more common than currently thought.